Analysis of Philippine remittances flow using country-level COVID-19 government responses - Hanapin, Ashley Khay; Orano, Mark Jucel (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This study provides a new approach to analyzing Philippine remittances flow by using the COVID- 19 government responses of both the Philippines and source countries in lieu of traditional determinants of remittances, which reflect migrant workers’ altruism. This study examines whether such an approach provides a reliable explanation consistent with the altruism hypothesis and whether COVID-19 government responses can be effective substitutes to the traditional determinants of remittances when a pandemic shock takes place. To represent COVID 19 government responses, the study utilizes four COVID-19 indices for the Philippines and each of the 11 sample source countries constructed from the Oxford COVID-19 Government Response Tracker data. The study employs Ordinary Least Squares (OLS) Regression to determine the relationship between remittances and COVID-19 government responses. The study utilizes one regression model for remittances and source country COVID-19 indices and another model for remittances and home country COVID-19 indices. To test the validity of these COVID-19 response-based specifications, the study examines how well they fare in econometric terms based on the OLS regressions. The results reveal that the first and second models are 65.91 percent and 38.64 percent accurate, respectively, in demonstrating the hypothesized effect of COVID 19 government responses on remittances. The study shows that when source and home country COVID-19 indices are less synchronized, the hypothesized effects become more prominent with the right signs and are statistically significant.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes appendices and bibliographical references.
Keywords: COVID-19 (Disease) -- Economic aspects -- Philippines; Emigrant remittances -- Philippines